Introduction: Historical Perspective on Contemporary Issues - Nelson, Adam (International Higher Education, 2014)
In the spring of 2013, the Worldwide Universities Network (WUN) commissioned a report to help university leaders think about the future of higher education. The network asked: what would the landscape of international higher education look like a generation from now? What challenges and opportunities lay ahead for universities, especially “global” research universities?